Pengembangan Media Monosida (Monopoli Sidoarjo) Berbasis Kearifan Lokal Untuk Meningkatkan Literasi Spasial Murid SMAN 1 Sidoarjo - inka_inka; Sigit Widodo, Bambang; Sri utami, Wiwik; Perdana Prasetya, Sukma; Lestari Sitohang, Lidya (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2026)
Low spatial literacy among students in geography learning is a problem that needs to be addressed through learning media innovation. This research aims to develop Monosida (Monopoly Sidoarjo) media based on local wisdom to improve spatial literacy of SMAN 1 Sidoarjo students. The research used Research and Development method with ADDIE model involving 36 grade X students as research subjects. Data were collected through spatial literacy tests, expert validation questionnaires, learning observations, and interviews. Analysis techniques used descriptive statistics, t-test, and thematic analysis. The results showed that Monosida media obtained a very valid category (4.3/5) from expert validators and was very practical (4.3/5) in implementation. The media was effective in improving students' spatial literacy with an average score increase of 27.8% from pretest to posttest (p<0.001, Cohen's d=2.03). Students' appreciation of local wisdom increased by 43.3%, and active participation in learning rose from 68.8% to 87.5%. The BBM concept (Berkesadaran/Conscious, Bermakna/Meaningful, Menggembirakan/Joyful) proved effective in integrating edutainment with contextual learning. Monosida media can be an innovative solution for geography learning that integrates local wisdom to improve spatial literacy and strengthen students' cultural identity.